Virtual Reality for Neurorehabilitation: Insights From 3 European Clinics. Issue 9 (27th September 2018) - O'Neil, Owen; Fernandez, Manuel Murie; Herzog, Jürgen; Beorchia, Marta; Gower, Valerio; Gramatica, Furio; Starrost, Klaus; Kiwull, Lorenz
Abstract: Virtual reality for the treatment of motor impairment is a burgeoning application of digital technology in neurorehabilitation. Virtual reality systems pose an opportunity for health care providers to augment the dose of task‐oriented exercises delivered both in the clinic, and via telerehabilitation models in the home. The technology is almost exclusively applied as an adjunct to traditional approaches and is typically characterized by the use of gamified exergames which feature task‐oriented physiotherapy exercises. At present, evidence for the efficacy of this technology is sparse, with some reviews suggesting it is the same or no better than conventional approaches. The purpose of this article is to provide real‐world insights on the adoption of a virtual reality by 3 European clinics in 3 different service delivery models. These include an inpatient setting for Parkinson disease, a kiosk model for pediatric neurorehabilitation, and a home‐based telerehabilitation model for neurologic patients. Motivations, settings, requirements for the pathology, outcomes, and challenges encountered during this process are reported with the objective of priming clinicians on what to expect when implementing virtual reality in neurorehabilitation.